Ultralow nitrogen-doped carbon coupled carbon-doped Co3O4 microrods with tunable electron configurations for advanced Li-storage properties. (10th December 2019) - Shi, Mingyuan; Huang, Zhe; Liu, Haimi; He, Jianwei; Zeng, Weihao; Wu, Qian; Zhao, Yufeng; Tian, Meiyue; Mu, Shichun
Abstract: Doping is a very effective way to optimize the electrochemical performance of electrodes by tuning the electron configurations on an atomic scale. Here, to obtain excellent Co3 O4 electrodes for lithium ion storage, a meaningful defect-engineering of carbon-doping Co3 O4 microrods strongly coupling with nitrogen-doped carbon (C–Co3 O4 @N–C) is designed and validated. Compared with unmodified Co3 O4 microrods, the defect-rich C–Co3 O4 @N–C microrod electrode features a remarkably high initial Coulombic efficiency of 84.5% and specific capacity of 1130 mAh g −1 at 0.2 A g −1, excellent cycling stability (1265 and 1036 mAh g −1 capacity retention after 110 and 500 cycles at 0.2 A g −1 and 1 A g −1, respectively) and superior rate capacity (452 mAh g −1 capacity retention after 3000 cycles at 5 A g −1 ). These results demonstrate that introducing rich defects by carbon dopants and nitrogen-doping carbon can effectively modulate the electron structure and accelerate the carrier transport of materials. This valid stratagem greatly elevates lithium-ion battery performance and can be further extended to other transition metal oxides and fields. Graphical abstract: Image 1 Highlights: Carbon doping effectively tunes electron configurations of Co3 O4, improving electron conductivity. Unique microrod structures can self-adapt to volume expansion during cycles. Ultralow nitrogen-doped carbon accelerates carrier diffusion of Co3 O4 electrodes. Coupling nitrogen-doped carbon with carbon doped Co3 O4 features high Li-storage properties.